2021
DOI: 10.3390/en14216948
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Monitoring and Static Data Analysis to Assess Energetic and Environmental Performances in the Wastewater Sector: A Case Study

Abstract: Real-time monitoring of energetic-environmental parameters in wastewater treatment plants enables big-data analysis for a true representation of the operating condition of a system, being still frequently mismanaged through policies based on the analysis of static data (energy billing, periodic chemical–physical analysis of wastewater). Here we discuss the results of monitoring activities based on both offline (“static”) data on the main process variables, and on-line (“dynamic”) data collected through a monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Di Cicco et al, 2021, for example, report a case study from the Agropoli WWTP (45,000 p.e.) in Italy where the average temperature of 22 • C and the average sub-acid pH values from 5 to 7 in the bioreactor form a potentially suitable medium for greenhouse growth of the emerging extremophilic thermoacidophilic microalgae with high potential for WWT and resource recovery [101].…”
Section: Temperature Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Di Cicco et al, 2021, for example, report a case study from the Agropoli WWTP (45,000 p.e.) in Italy where the average temperature of 22 • C and the average sub-acid pH values from 5 to 7 in the bioreactor form a potentially suitable medium for greenhouse growth of the emerging extremophilic thermoacidophilic microalgae with high potential for WWT and resource recovery [101].…”
Section: Temperature Controlmentioning
confidence: 99%
“…The majority of algae grow in mediums with pH levels between 7 and 9 [8,102]. However, some algae are alkalophilic with preferable pH values of 9 or even 10 and above, while other strains, such as the extremophilic thermoacidophilic microalgae, prefer mediums with pH values of 5-6, which were measured in the effluent of real WWTPs [8,101,102].…”
Section: Ph Variation Transfer Of Co 2 and O 2 Oversaturation Inhibitionmentioning
confidence: 99%
“…In this context, it is necessary to emphasize the considerable efforts being sought in the European Union and National States with the "Green New Deal" programs that aims to implement policies for the minimization of CO 2 emissions, the development of renewable energies, as well as the recovery of resources from waste matrices, such as solid and liquid wastes [30][31][32][33][34][35]. These energy-environmental optimization goals can only be realized by introducing "smart" methodologies, protocols and technologies in the industrial production processes, as relevant scientific literature has already demonstrated the results of such applications in a variety of industrial sectors related to citizens' lives [36][37][38][39][40][41][42][43][44][45][46][47]. At the international level, efforts have been undertaken for some years now to fulfil this objective through the activation of specific policies and the encouragement of research and development projects.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, if the shipping sector was considered as a distinct country, it would rank as the sixth largest emitter of greenhouse gases (GHG) in the world, right between Japan and Germany. The maritime sector is significantly responsible for a large part of emissions of marine pollutants (substance release, thermal and noise pollution) and atmospheric pollutants (NOx, SOx, PM) (Brenna et al 2020 ), while its share of GHG emissions currently corresponds to 2–3% on a global scale (Smith et al 2014 ), exceeding or almost equalling many other sectors that provide services of extreme importance to humans, such as the water (di Cicco et al 2019 ), waste stream treatment (di Cicco et al 2021 ) and telecommunications sectors (Vetromile et al 2021 ). But this number could still increase, because the demand for maritime transport is growing rapidly and so are the associated fuel consumption emissions.…”
Section: Introductionmentioning
confidence: 99%